Guidelines for Electronic Links to International Conferences An Analytical Study on a Sample of International Conferences of the College of Humanities at the University of Sulaimani - Saeed, اAsst.Prof.Dr.Lana Saber Mohammed Saeed; Marf, Asst.L.Chro.Shahab Marf (Sulaimani Journal for Humanities, 2025)
International conferences are vital platforms for exchanging ideas and opinions among countries and organizations, playing a significant role in addressing pressing global issues. By providing opportunities for dialogue, these conferences contribute to building trust and exchanging perspectives on issues such as climate change, sustainable development, human rights, and international security. They also serve as policy-making forums, where agreements and treaties that impact the international community are discussed and drafted. International and local conferences are important events that bring together individuals and diverse entities to exchange ideas and information, discuss contemporary issues, and foster cooperation among stakeholders. Public relations plays a vital role in organizing these events and ensuring their success, contributing to building a positive image for the organizers and promoting effective communication with the public and media. Conferences also promote the exchange of knowledge and expertise, contributing to innovation and collaboration. Furthermore, they help stimulate international cooperation by strengthening relations between countries in various fields such as the economy, the environment, and health. By attracting media and public attention, conferences contribute to shaping public opinion and supporting global campaigns. Ultimately, these events provide an opportunity to build strategic partnerships that strengthen global cooperation and help address shared challenges. In the digital age, technology plays a pivotal role in enhancing public relations during conferences. Technologies such as live streaming and recording can be used to expand audience reach, in addition to developing dedicated conference platforms that allow participants to access important information. Social media also contributes to enhancing interaction among participants, creating an atmosphere of dialogue and discussion. A deep understanding of public relations techniques is essential for anyone seeking to organize successful conferences, as it contributes to creating an environment of cooperation and constructive dialogue, leading to effective results at both local and international levels. The research consists of two parts: the first part, the research methodology, including the problem, objectives, significance, previous studies, and methodological procedures; the second part, the research theory, which relates to the management of international conferences; and the final part, the analytical results, conclusions, recommendations, suggestions, and bibliography.